Auto-segmental analysis of consonant deletion in thè spoken french of ijebu undergraduate french learners in selected universities in south sest of Nigeria (2015)
In communication, each spoken word is created out of thè phonetic combination of a limited set of vowel and consonant speech sound units. Deletion, which involves loss of segment involving vowel and consonants, is a common phonological process in language. Existing studies have examined deletion in several languages and dialects with less attentionpaid to thè spoken French of Ijebu Undergraduates. This article, therefore, examined consonant deletion in thè spoken French of forty-four Ijebu Undergraduate French Learners (IUFLs) in Selected Universities in South West of Nigeria, with a view to establishing thè dominance of consonant deletion in thè spoken French of IUFLs. The data collection was through tape-recording of participants' production of 30 sentences containing both French vowel and consonant sounds, while Goldsmith's Auto-segmental theory of phonology (1990) was used to analyse instances of consonant deletion by thè IUFLs. The results revealed inappropriate consonant deletion in thè initial, mediai and final positions in thè French speech communication of IUFLs.